2016
DOI: 10.1111/jph.12468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clove Essential Oil as a Mycobiocide Against Rhizopus stolonifer and Fusarium solani, Tuber Rot Causing Fungi in Yam (Dioscorea rotundata Poir.)

Abstract: To exploit natural products for plant disease control, the essential oil of Syzygium aromaticum (L.) Merr. & Perr. (clove) was investigated for its antifungal activity against Rhizopus stolonifer and Fusarium solani, the postharvested yam tuber rot pathogens. The essential oil was obtained by hydrodistillation using a Clevenger‐type apparatus. The chemical composition of the oil was determined by gas chromatography and gas chromatography coupled with mass spectrometry. Antifungal activities of the oil were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…Thus, under curative conditions, 10 h of separation between G. citri-auriantii inoculation and lemon treatments could be enough for the fungus to invade the fruit cells and HP-β-CD-thymol complex would be less able to control the decay spread. Thus, Sameza et al [ 29 ] reported that infection control becomes difficult once a pathogen penetrates plant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, under curative conditions, 10 h of separation between G. citri-auriantii inoculation and lemon treatments could be enough for the fungus to invade the fruit cells and HP-β-CD-thymol complex would be less able to control the decay spread. Thus, Sameza et al [ 29 ] reported that infection control becomes difficult once a pathogen penetrates plant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…9 Although the synthetic fungicides are effective, the development of fungal resistance, toxicity to non-target organisms and environmental problems is due to its continuous or repeated application. 10 The search for antifungal compounds from natural sources has increased over the last decade, and plants continue to be a major source of biologically active compounds that may provide lead structures for the development of new drugs. 11 In this scenario, essential oils constitute a rich source of bioactive chemicals and have been recently pointed out as a promising alternative against the pathogenic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…To solve problems above many scientists have increased interests in finding safer substances including plant extracts and plant secondary metabolites with fungicidal activities (Copping and Menn 2000;Yoon et al 2011;Sameza et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic fungicides have been widely applied as preventive or curative measures to control plant diseases over the past several decades, but the continuously repeated and excessive applications of synthetic fungicides have resulted in fungus resistance (Gisi et al 2002;Steffens et al 1996;Zhang et al 2006), residual toxicity in food (Navarro et al 2011) and disruption of ecosystem (Tu et al 2011). To solve problems above many scientists have increased interests in finding safer substances including plant extracts and plant secondary metabolites with fungicidal activities (Copping and Menn 2000;Yoon et al 2011;Sameza et al 2016).…”
Section: Introductionmentioning
confidence: 99%